Arkitektur som forskningsfelt - Haugdal, Elin (Nordlit, 2015)
This article gives a brief overview of research on architecture by art historians at UiT The Arctic University of Norway, and addresses some challenges for research on buildings within the discipline of Art history generally, and in the northernmost parts of Scandinavia particularly. Art history’s history of monuments has during the last four to five decades been expanded by new theoretical and aesthetic perspectives on architecture, and is questioned by a more comprehensive and socially distinguished research on the built environment. Researchers on architecture in the northern areas experience these tensions more directly, which thus provides an opportunity to question methods of writing architectural history.